Risk Management in Organisations : an integrated case study approach - Woods, Margaret, 1954- (New York: Routledge, 2022)
"Risk management is vital to organisational success, from government down to small businesses and the discipline has developed rapidly over the last decade. Learning lessons from the good and bad practice of others is a key feature of this book, which includes multiple illustrative examples of risk management practice, in addition to detailed case studies. Combining both theory and practice, the early chapters compare the ISO31000 and COSO Enterprise Risk Management frameworks, and the relevant regulatory regimes in both Europe and the USA. The core of the book is three highly detailed cases studies of risk management in the manufacturing (Akzo Nobel), retail (Tesco) and public sectors (Birmingham City Council). Using the lessons learned from the case studies, together with material from elsewhere, the author then outlines four lessons for risk managers that can be used in any organisation seeking to develop a truly enterprise-wide risk management system. This completely revised edition contains updates on regulations and practice, together with new chapters covering technology risk and Covid 19, which are major risks faced by all organisations today. As such the book is essential reading for risk management professionals and postgraduate and executive learners"--
Keywords: Risk management; Management -- Research